A Facile Synthesis of Thioacids from N-Acylbenzotriazoles - Khaybullin, Ravil; Panda, Siva S.; Al-Youbi, Abdulrahman O.; Katritzky, Alan R. (Synlett, 2014)
Protected amino/peptide thioacids have been synthesized in pure form in excellent yields and with retention of chirality by using protected aminoacyl- and peptidoylbenzotriazoles as active intermediates.
Keywords: amino acids; peptides; chirality; thioacids; benzotriazole methodology